Mastodynia - Bonilla-Sepulveda, Óscar Alejandro; Giraldo-Santa, Diana Carolina (CES Medicina, 2019)
Introduction: Mastalgia is a frequent clinical symptom in general and gynecological medicine consultation. The objectives of this bibliographical review are: to define the diagnostic concept, classification and treatment of mastalgia. Methods: literature search in Pubmed, Scielo, Cochrane and Google Scholar, using the MeSH terms: mastodynia, mastalgia, breast pain, chest pain. The search limits were: full texts in English and Spanish, in humans and published during the last 10 years. Results: the physiopathology of the mastodynia is not caused by a single mechanism, but by different causes with independent pathways. The main mechanisms are hormonal, mammary density, neuropathic and extra-mammary. Conclusion: It is important to know the pathophysiology and classification of mastodynia, due to its therapeutic implications and possible association with breast cancer.